2017
DOI: 10.1063/1.4991208
|View full text |Cite
|
Sign up to set email alerts
|

Effect of thermal stress on HSP90 expression of Bali cattle in Barru district, South Sulawesi

Abstract: Morphometric study of mantis shrimp Harpiosquilla harpax (De Haan, 1844) Abstract. Heat shock protein 90-kDa is induced stress protein that expressed in response to stress and play crucial roles in environmental stress tolerance and adaptation. This study aimed to determine effect of environmental heat stress on the HSP90 expression of Bali cattle. Heat stress was measured by temperature humidity index in the morning and evening across 5-days on August 2016. The blood samples of Bali cattle were taken from v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Though there are many HSP genes, thermo tolerance in livestock animals is primarily associated with the HSP70 and HSP90 genes. The most common and temperature-sensitive is HSP90, which is thought to play an important role in environmental stress and thermal adaptation (Gade et al, 2010;Aritonang et al, 2017;Puteri et al, 2018). In summer, higher levels of expression of proteins of the HSP70 and HSP90 families have been observed in a variety of livestock species (Archana et al, tolerance, milk production, fertility, and disease susceptibility in livestock (Shergojry et al, 2014a;Kumar et al, 2015;Bhat et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Though there are many HSP genes, thermo tolerance in livestock animals is primarily associated with the HSP70 and HSP90 genes. The most common and temperature-sensitive is HSP90, which is thought to play an important role in environmental stress and thermal adaptation (Gade et al, 2010;Aritonang et al, 2017;Puteri et al, 2018). In summer, higher levels of expression of proteins of the HSP70 and HSP90 families have been observed in a variety of livestock species (Archana et al, tolerance, milk production, fertility, and disease susceptibility in livestock (Shergojry et al, 2014a;Kumar et al, 2015;Bhat et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Responses to thermal stress are enhanced in Bos taurus indicus breeds, which are better able to regulate their metabolism in response to heat stress as compared to Bos taurus taurus breeds . A study performed on Bali beef cattle (Bos sondaicus) found that differences in environmental conditions in the morning and afternoon did not affect hsp90 expression (Aritonang et al, 2017). observed that HSP90AA1 (hsp90) gene expression was significantly higher during heat stress at 45 °C in Sahiwal (Bos taurus indicus) and Frieswal (Bos taurus indicus × Bos taurus taurus crossbreed) breeds in comparison to the heat stress at 39 °C.…”
Section: Discussionmentioning
confidence: 99%